A Cross-Sectional Study of Patient's Satisfaction Towards Services Received at Tertiary Care Hospital on OPD Basis - Bilkish N Patavegar; Sangita C Shelke; Prakash Adhav; Manjunath S Kamble (Medsci Publications, 2012)
Objective: The main objective of the study is to measure the satisfaction of OPD patients in tertiary care hospital and to know the relationship between various determinants & OPD patient's satisfaction. Materials and methods: The present cross sectional study was conducted among 450 patients attending the outpatient departments (OPDs) of Sassoon General Hospital Pune during 6 months period. Systemic random sampling was used for patient selection. Results: Maximum number of patients i.e. 197(43.78%) were in the age group of 49 and above. About 61% patients were females. About cleanliness of waiting area 44.5% patients were found unsatisfied. About explanation of treatment by pharmacist 77% patients were satisfied. 91% patient said that OPD timings were convenient. 176 (39.12%) patients had to wait less than 30 min before consulting doctor. Conclusion: According to the patient's opinion, the study showed good satisfaction with respect to registration services, doctor services, nurse services, lab services and pharmacy staff services.